The effectiveness of microneedling in the treatment of post-COVID-19 hair disorders - Cassimiro, Alice Pires; Ferreira, Mary Magdalene Costa; Santos, Thaina Lima; Mascarenhas, Maria Tereza Martins; Bacelar, Solange Negreiros de Almeida; Furtado, Ana Eugenia Araujo; Soares, Karla Virginia Bezerra de Castro; Penha, Ludmilia Rodrigues Lima Neuenschwander; Falcão, Ríndhala Jadão Rocha; Sousa, Julia De Aguiar Baldez (Seven Editora, 2023)
Patients who were contaminated by SARS-CoV-2 developed an infectious picture of non-cicatricial alopecia of the type’s alopecia areata - AA, androgenetic alopecia - AGA and increased cases of telogen effluvium - ET, and for alopecia areata and androgenetic alopecia was observed worsening of these diseases in cases of patients already being carriers of this pathology. Microneedling therapy has been used to treat hair disorders, regenerate follicles and seek balance in the capillary cycle. Such treatment has been shown to be quite advantageous when compared to other therapies that treat SARS-CoV-2 viral infection. This study aims to demonstrate the efficacy of microneedling techniques in the treatment of hair disorders, considering that the effectiveness of the treatment is showing highly promising results in the face of exacerbation of capillary disorders caused by SARS-CoV-2 viral infection. This article is characterized as an integrative, descriptive and qualitative review. The work was composed of specialized bibliography, consisting mainly of articles and scientific journals published in English and Portuguese, consulted the Medline databases (Medical Literature Analysis and Retrieval System Online); Google Scholar and Virtual Library – CEUMA, using the descriptors "COVID-19" and "hair disorder", "COVID-19" and "alopecia", "microneedling" and "treatment" and "alopecia". Microneedling accelerates the inflammatory process, providing skin revascularization, tissue regeneration and hair follicle stimuli. It is a safe method with a low risk of side effects, showing effective results in androgenetic alopecia-AGA. alopecia areata-AA and telogen effluvium-ET. DOI: https://doi.org/10.56238/emerrelcovid19-057